2010
DOI: 10.48550/arxiv.1005.1627
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Heavy Quark Production in p+p and Energy Loss and Flow of Heavy Quarks in Au+Au Collisions at sqrt(s_NN)=200 GeV

A. Adare,
S. Afanasiev,
C. Aidala
et al.

Abstract: Transverse momentum (p e T ) spectra of electrons from semileptonic weak decays of heavy flavor mesons in the range of 0.3 < p e T < 9.0 GeV/c have been measured at midrapidity (|η| < 0.35) by the PHENIX experiment at the Relativistic Heavy Ion Collider in p+p and Au+Au collisions at √ sNN = 200 GeV. In addition, the azimuthal anisotropy parameter v2 has been measured for 0.3 < p e T < 5.0 GeV/c in Au+Au collisions. The nuclear modification factor RAA with respect to p+p collisions indicates substantial energy… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(92 citation statements)
references
References 45 publications
(65 reference statements)
3
89
0
Order By: Relevance
“…Furthermore, because the charm quark is massive compared to light quarks, its v 2 is likely not the same as the light quarks [33,34]. The charm quark v 2 has not been measured directly at RHIC, but only indirectly from the electrons from semi-leptonic decays [35,36]. In that measurement there is a mixture of bottom and charm sources [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, because the charm quark is massive compared to light quarks, its v 2 is likely not the same as the light quarks [33,34]. The charm quark v 2 has not been measured directly at RHIC, but only indirectly from the electrons from semi-leptonic decays [35,36]. In that measurement there is a mixture of bottom and charm sources [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…The electrons from J/ψ decay contribute noticeably to the observed non-photonic electron signal as pointed out in Ref. [38]. In order to estimate the contribution from J/ψ → e + e − to the non-photonic electron yield, we combine the measured differential J/ψ cross-sections from PHENIX [39] and STAR [40].…”
Section: G Contribution From Vector Mesonsmentioning
confidence: 99%
“…At high transverse momentum, this mechanism of electron production is dominant enough to reliably subtract other sources of electrons such as γ conversions and π 0 Dalitz decays. STAR [9] and PHENIX measurements [10] in central Au+Au collisions have shown that the high-p T yield of electrons from semileptonic charm and bottom decays is suppressed relative to properly scaled proton-proton collisions, quantified in the nuclear modification factor R AA [9] (cf. Figure 1).…”
Section: Single Electron R Aamentioning
confidence: 99%
“…This finding is not in line with expectations from the dead-cone effect. Energy-loss models incorporating contributions from charm and bottom do not describe the observed suppression sufficiently well (see discussions in [9,10]). Although it has been realized that energy loss of heavy quarks by elastic parton scattering causing collisional energy loss is probably of comparable importance to energy loss by gluon radiation, yet the quantitative description of the suppression is still not satisfying.…”
Section: Single Electron R Aamentioning
confidence: 99%